THE USE OF DIGITAL STORYTELLING TO ENHANCE THE STUDENTS’ SPEAKING ABILITY - Errika Wafa; Nur Chakim (ELite Journal : International Journal of Education, Language, and Literature, 2022)
The purpose of this study is to identify whether the use of digital storytelling can enhance students' speaking ability in learning English. The research was conducted using a descriptive quantitative method of pretest-posttest control group design for 8th grade junior high school students in Surabaya, Indonesia. A total of 40 students who were divided equally into the control group and the experimental group participated in this study. Students who were included in the experimental group were given treatment by learning English using digital storytelling, while students in the control group were not given this treatment. Based on the results of statistical analysis of the pretest and posttest scores conducted on the two groups of students, it shows that there is a significant difference in the posttest results of the two groups. The average score of the group of students who were not given treatment only increased by 17.02% while the group of students who received treatment increased by 26.79%. The results of the independent samples t test using the Mann-Whitney method at a significance level of 95% (? = 0.05) also showed that the t value was 109.500 < t table 127.000 and the p-value was 0.009 < 0.05. This means that there is a significant difference in posttest results between the group that was given the treatment of digital storytelling and the group that was not given the treatment, so it can be concluded that the use of digital storytelling can enhance students' speaking ability in learning English.